Fundamental Psychopathology: for a despatologizing understanding of sexual diversity - Zerbinati, Joao Paulo [UNESP]; Toledo Bruns, Maria Alves de (Univ Federal Fluminense, Inst Ciencias Sociedade & Desenvolvimento Regional, 2019)
This paper aims to discuss a field of knowledge for understanding and investigating sex and gender diversity that does not simply take them as a disease, but can understand the suffering involved. Challenging, though a necessary proposal to advance towards an integral understanding of the contemporary subject which does not neglect the human dimension of his/her pathos. In this sense, we turn to Fundamental Psychopathology, a field of inter-scientific research initiated by Pierre Fedida, in University of Paris 7, which invests in the interlocution of multiple positions of knowledge for the understanding of the pathos experience as its original meaning, its etymological root and Greek tradition: passion and suffering. The Fundamental Psychopathology of psychoanalytic orientation meets the need to think about research proposals that are potent in the analysis and understanding of sexuality beyond a pathological, naturalizing and reductionist understanding.
Keywords: Sexuality; sexual diversity; fundamental psychopathology